MANAJEMEN BENCANA BANJIR OLEH BADAN PENANGGULANGAN BENCANA DAERAH KABUPATEN KAMPAR - Galih Razuna Alghifari; Febri Yuliani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
Disaster management is an action taken at the time before, during, and after disasters. Kampar Regency is one of regencies in Riau Province experienced frequent flood events in some regions. In addition due to the overflow of rivers in Kampar regency result of the opening of the door power (hydropower) Long Koto Kampar, flooding in Kampar also be caused by heavy rains. The purpose of this study was to determine how the flood disaster management conducted by the Regional Disaster Management Agency (BPBD) Kampar and to determine the factors inhibiting the flood disaster management. The research is a qualitative research with descriptive approach. The collection of data is needed both primary data and secondary data were collected through interviews, observation and documentation and then analyzed so that it can be deduced from existing research problems. The results of this study found that implementation of disaster management conducted by the Regional Disaster Management Agency (BPBD) Kampar not implemented to the fullest, it is caused by several factors inhibiting the ability of human resources, people, budgets, and organizational structures that are not performing their duties and functions. Keyword: Disaster Management, Disaster Management Agency